2012
DOI: 10.1161/strokeaha.111.632943
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Cerebral Damage

Abstract: Abstract-In the human brain, Ϸ30% of the energy is spent on synaptic transmission. Disappearance of synaptic activity is the earliest consequence of cerebral ischemia. The changes of synaptic function are generally assumed to be reversible and persistent damage is associated with membrane failure and neuronal death. However, there is overwhelming experimental evidence of isolated, but persistent, synaptic failure resulting from mild or moderate cerebral ischemia. Early failure results from presynaptic damage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(129 citation statements)
references
References 135 publications
1
99
0
Order By: Relevance
“…Experimental evidence showed that persistent synaptic failure may result from mild or moderate cerebral ischemia involving both pre-and postsynaptic components of the hippocampus. 34 Although there was an acute decrease in CBF at the time of blood or saline injection, we did not find differences between CBF or glucose À ) analysis. Significantly increased NO was found in the hippocampus (A), Pp0.001, Student's t-test) but not cerebral cortex (B) in subarachnoid hemorrhage (SAH) group as compared with saline controls.…”
Section: New Findingsmentioning
confidence: 49%
“…Experimental evidence showed that persistent synaptic failure may result from mild or moderate cerebral ischemia involving both pre-and postsynaptic components of the hippocampus. 34 Although there was an acute decrease in CBF at the time of blood or saline injection, we did not find differences between CBF or glucose À ) analysis. Significantly increased NO was found in the hippocampus (A), Pp0.001, Student's t-test) but not cerebral cortex (B) in subarachnoid hemorrhage (SAH) group as compared with saline controls.…”
Section: New Findingsmentioning
confidence: 49%
“…The global ischemia model used here is clinically related to cardiac arrest or cardiac surgery (Hofmeijer and van Putten, 2012). Although this model does not recapitulate more clinically relevant middle cerebral artery occlusion models (Dirnagl et al, 1999), we can precisely control the duration of ischemia to within seconds and can rapidly alternate between the initiation of ischemia or reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In this condition, the region of the brain that is most damaged, the ischemic core, fully depends on oxygen and glucose provided by the affected blood vessel, while the penumbra region, the area surrounding the infarcted core, is not as compromised due to a limited supply of components required for the metabolism derived from the collateral circulation. Glucose is the main substrate for cerebral energy production (Hofmeijer and van Putten, 2012) and during stroke the oxygen carried by the blood is much less than that required for complete oxidation of its content of glucose. Under these conditions, glycolysis may persist after oxygen has been depleted, but the reduction of oxidative metabolism of glucose leads to decreased ATP levels, while ADP and AMP levels increase (Hertz, 2008), causing a disruption of ionic homeostasis (Hansen, 1985), opening of anion channels (Kimelberg and Mongin, 1998), plasma membrane depolarization (Lipton, 1999), release of glutamate through astrocytic hemichannels (Ye et al, 2003) and downregulation of glutamate transporters (Harvey et al, 2011).…”
Section: Brain Ischemiamentioning
confidence: 99%